2014
DOI: 10.1016/j.cub.2014.05.006
|View full text |Cite|
|
Sign up to set email alerts
|

Resolution Mediator Chemerin15 Reprograms the Wound Microenvironment to Promote Repair and Reduce Scarring

Abstract: SummaryDisorders of cutaneous repair can cause disability or death given that skin functions as a protective barrier against the external environment. The inflammatory response triggered by tissue damage is thought to play both positive (e.g., pathogen-killing) and negative (e.g., scarring) roles in repair [1–3]. Inflammatory resolution mediators such as chemerin15 (C15) control the magnitude and duration of the inflammatory response; however, their role in wound repair and scarring is unknown [4–8]. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…Conditional depletion of macrophages has been shown to reduce liver fibrosis when induced early, but had pro-fibrotic effects when induced at advanced stages of fibrosis (Duffield et al, 2005). Macrophages are now understood to exist in a spectrum of different activation (polarization) types that control different phases of healing and it will be important to target specific macrophages to achieve scarless healing (Cash et al, 2014;Davies et al, 2013;Friedman et al, 2013;Lucas et al, 2010;Mantovani et al, 2013;Martinez and Gordon, 2014;Mosser and Edwards, 2008;Wynn et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Conditional depletion of macrophages has been shown to reduce liver fibrosis when induced early, but had pro-fibrotic effects when induced at advanced stages of fibrosis (Duffield et al, 2005). Macrophages are now understood to exist in a spectrum of different activation (polarization) types that control different phases of healing and it will be important to target specific macrophages to achieve scarless healing (Cash et al, 2014;Davies et al, 2013;Friedman et al, 2013;Lucas et al, 2010;Mantovani et al, 2013;Martinez and Gordon, 2014;Mosser and Edwards, 2008;Wynn et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Chemerin-15, a synthetic peptide, signals via Cmklr1 to elicit many of the same biological effects as chemerin (Cash et al 2008). Cash et al (2014) reported that chemerin-15 alters collagen deposition in injured skin. Since chemerin-15 and chemerin signal via Cmklr1 (Cash et al 2008;Bondue et al 2011), it is plausible that chemerin-Cmklr1 signaling modifies collagen deposition in skin as well as in other organs, including the lungs, a phenomenon that would significantly impact the quasistatic elastic properties of the respiratory system.…”
Section: Effect Of O 3 and Ccrl2 Deficiency On Lung Injury And Lung Imentioning
confidence: 99%
“…These pathways offer enormous potential to therapeutically modulate the resolution phase of inflammation and thus impact on the repair process (158,160). Indeed, we have previously shown that topical application of the peptide resolution mediator chemerin15 dampens the wound inflammatory response and skews the Mϕ phenotype to one typically associated with repair (reduced inducible NOS and TNF-α; increased arginase-1), resulting in accelerated healing with reduced scarring (161).…”
Section: Harnessing Proresolving Pathways To Drive Repairmentioning
confidence: 98%